Implementation of SQ3R Method in Improving the Students’ Basic Reading Skill - Imam Nur Aziz (STAI Miftahul Ula Nganjuk, 2020)
The SQ3R method is an increasingly popular and widely used reading method. This method is considered as a method of reading which is quite effective and can produce good understanding. SQ3R is a method of reading to find the main ideas and supporters of the main ideas also help the reader to remember longer. SQ3R is an excellent method for intensive and rational reading. This method is more appropriate for study needs. Because this method is designed according to levels that allow students to learn systematically, and efficiently. The study used qualitative approach by collecting data, arranged in a systematic, factual and accurate. This study used in-depth interviews, observations, and documentation. The results obtained from the implementation of the SQ3R method in improving reading skills at MI Uyunul Ulum Gayam Bojonegoro are good enough, that the SQ3R method can improve students' reading skills. It bocomes a sollution to build student creativity and also makes the students dare to advance in order to uphold the progress of the institution.